A Switchable Cross‐Species Liquid Repellent Surface. Issue 8 (16th December 2016) - Huang, Yu; Stogin, Birgitt Boschitsch; Sun, Nan; Wang, Jing; Yang, Shikuan; Wong, Tak‐Sing
Abstract : A switchable cross‐species liquid‐repellent surface is developed that can rapidly switch between two distinct liquid‐repellent modes: i) the superhydrophobic mode, modeled after lotus leaves, and ii) the slippery mode, modeled after the pitcher‐plant peristome. Adaptive liquid repellency and programmable fog harvesting are demonstrated as application examples for the new switchable surface.